Efektivitas Pelaksanaan One Day Service (ODS) di Badan Pelayanan Perijinan Terpadu Kabupaten Sidoarjo - Christin Yuliani; Isna Fitria Agustina (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aimed to describe the government's role on the public service providers in implementing One Day Service Program (ODS) in the Integrated Licensing Service Agency, Sidoarjo Regency and determine its supporting and inhibiting factors program. The method used descriptive qualitative. The data collected from Licensing Services Integrated Agency, Sidoarjo Regency. The informants in this research are Head of Licensing Services Integrated Agency Sidoarjo Regency, head of business license sector, Customer Service (CS), and the customer. The results showed that the effectiveness of One Day Service (ODS) implementation in the scope of district by Licensing Services Integrated Agency, Sidoarjo Regency run effectively and accordance with six (6) service standards set by the government. It was procedures, the time of completion, cost of service, product service, and facilities. Some of supporting factors in the effectiveness of its program included employees of Licensing Services Integrated Agency, Sidoarjo Regency which has considerable experience and have the ability / expertise; the availability of complete facilities included computer / laptop, printer, desk, chair, internet, and other facilities. While, some of inhibiting factors effectiveness of its program included lack of socialization time, lack of awareness of officials at the district level, and lack of an active role of village officials.